Biodestructive plasticizer for polyvinyl chloride based on tertiary amide of undecenoic acid - Rogalsky, Sergiy; Tarasyuk, Oksana; Dzhuzha, Oleh; Bodachivska, Larysa; Venher, Iryna; Papeikin, Oleksii (Problems of Environmental Biotechnology, 2021)
The synthesis of a new plasticizer for PVC, namely N, N-dibutyluncecenolamide, was carried out, and its biodegradability was studied.